Optimizing the quality of breast cancer care at certified german breast centers - Brucker, Sara; Wallwiener, Markus; Kreienberg, Rolf; Jonat, Walter; Beckmann, Matthias W.; Bamberg, Michael; Wallwiener, Diethelm; Souchon, Rainer (Strahlentherapie und Onkologie, 2011)
Purpose: A voluntary, external, science-based benchmarking program was established in Germany in 2003 to analyze and improve the quality of breast cancer (BC) care. Based on recent data from 2009, we aim to show that such analyses can also be performed for individual interdisciplinary specialties, such as radiation oncology (RO). Methods: Breast centers were invited to participate in the benchmarking program. Nine guideline-based quality indicators (QIs) were initially defined, reviewed annually, and modified, expanded, or abandoned accordingly. QI changes over time were analyzed descriptively, with particular emphasis on relevance to radiation oncology. Results: During the 2003–2009 study period, there were marked increases in breast center participation and postoperatively confirmed primary BCs. Starting from 9 process QIs, 15 QIs were developed by 2009 as surrogate indicators of long-term outcome. During 2003–2009, 2/7 RO-relevant QIs (radiotherapy after breast-conserving surgery or after mastectomy) showed considerable increases (from 20 to 85% and 8 to 70%, respectively). Another three, initially high QIs practically reached the required levels. Conclusion: The current data confirm proof-of-concept for the established benchmarking program, which allows participating institutions to be compared and changes in quality of BC care to be tracked over time. Overall, marked QI increases suggest that BC care in Germany improved from 2003–2009. Moreover, it has become possible for the first time to demonstrate improvements in the quality of BC care longitudinally for individual breast centers. In addition, subgroups of relevant QIs can be used to demonstrate the progress achieved, but also the need for further improvement, in specific interdisciplinary specialties.
Gesehen am 23.06.2022